Validation of MUAC Cut-Offs of WHO for Diagnosis of Acute Malnutrition among Children under 5 Years in Karachi, Pakistan - Qadri, Mehreen; Baig, Lubna Ansari; Ahmer, Zaeema; Asim, Aimen; Aly, Syed Moin (International Journal of Child Health and Nutrition, 2022)
Objective: To validate the WHO recommended Mid-Upper Arm Circumference (MUAC) cut-offs for acute malnutrition screening in children younger than five in Karachi, Pakistan. Methods: A cross-sectional study was conducted, including an anthropometric examination following WHO guidelines. Height was measured using Stadiometer and Infantometer. The link between MUAC and Weight-for-Height-Z score (WHZ) for different cut-offs of MUAC for Moderate Acute Malnutrition (MAM) and Severe Acute Malnutrition (SAM) was shown using Receiver Operator Characteristics (ROC) curves and the Youden index. Sensitivity and specificity of MUAC <11.5 cm and ≥11.5 to <12.5cm were determined using WHZ scores of -3 Standard Deviation (SD) and ≥-3 to <-2 SD for SAM and MAM, respectively. Results: Among 499 children, as per WHZ score, 9.6% and 27.1% had SAM and MAM, respectively, whereas according to MUAC, 6.4% and 3.6% had MAM and SAM, respectively. At the maximum value of the Youden index of 55.6%, an optimum cut-off of 12.7cm for screening of SAM with MUAC was found compared to the recommended cut-off of 11.5cm. Similarly, at the maximum value of the Youden index of 57.7%, an optimum cut-off of 13.9cm for screening of MAM with MUAC was found compared to the recommended cut-off of 12.5cm. Conclusion: The current MUAC cut-off of WHO for screening SAM and MAM cases captures only a small percentage of children under five. This needs to be revised to capture children with acute malnutrition for timely treatment in Pakistan.